Fenomena Santai Dalam Kehidupan Masyarakat Desa Paul Kabupaten Tapin - Dahlawi, Muhammad; Damaiyanti, Varinia Pura (Prodi Sosiologi FISIP ULM, 2024)
There are similarities between Khaldun and Veblen ideas regarding the social change in contemporary society and both are also influential in forming leisure studies which are still rarely discussed and often overlooked in current social phenomena. This research aims to understand the leisure phenomenon by exploring all leisure activities and their influence on the lives of the people of Paul Village. This research uses social change theories and sociology of consumption theories. This design of research is post-qualitative and postmodernist paradigms. Data collection techniques through observations, interviews and documentations. This research took place from October 2022 to July 2023. Research results shows that the people of Paul Village leisure through watching television at the patrol post, karaoke, online games and shopping activities at the mobile vegetable market. Recent social changes have made it easier for residents of Paul village to do leisure activities every day. Television is an interesting spectacle when midnights at the patrol post and a remedy for tiredness from the daily work routine. Karaoke has become a routine to using free time when the holidays arrive and a means of nostalgia for the past. Then online games as a form of entertainment consumption for today's teenagers in Paul Village. Shopping for vegetables is now easy for the residents of Paul village with the presence of a vegetable seller driving in front of their house every morning. All of these activities show leisure phenomenon is formed from the consumption of advanced technology products and the consumption of media devices, which has led to an increase in the consumption patterns of the people of Paul Village. Reasonable technology consumption patterns will make communication easier and happier in the lives of the residents of Paul village. However, excessive consumption patterns of technology products bring bad effects such as individualism, hedonism, wasting time and useless facilities.